TI Verde: Uma Proposta de Economia Energética usando Virtualização - da Silva, Luana Barreto; Bomfim, Leonardo Henrique da Silva; Junior, George Leite; de Oliveira, Marcelino Nascimento (Interfaces Científicas - Exatas e Tecnológicas, 2015)
Information Technology (IT) is one of the main responsable for enviroment troubles. This is a challenge to be overcome by IT Managers to reduce the cust and the maintenance of datacenteres. To promote the user of computer resources on a efficient and less harmfull to enviroment, the Green IT method propose sustainable ways to support a datacenter. One of those ways is the datacenters virtualization, which means that one physical server has virtual ones, working as singles server. It is important to analyze the viability of keep a virtualized datacenter by the analysis of availability of the servers. If the use of virtualization enables a cost reduction, it can also make the system more susceptible to downtime. This work analyzes the availability of two environments, one with a virtualized server and the other with non-virtualized servers. The services offered are e-mail, DNS, Web Server and File Server, a typical scenario in many companies. It is developed a case study using analytical modeling with Fault Tree and Markov Chains. The Fault Tree is used to model the servers and Markov Chains to model the behavior of each component of hardware and software. The non-virtualized environment is composed of four servers, each one providing specific services, while the virtualized consists of a single server with four virtual machines, each one providing a service. By analyzing the models developed, the results show that although the non-virtualized system has less downtime, because has less dependence between the services, the difference in this case is 0.06% annually, becomes irrelevant when compared to the benefits brought by virtualization.